Effects of high-fat diet on sympathetic neurotransmission in mesenteric arteries from Dahl salt-sensitive rat - Alula, Kibrom M. (Auton Neurosci, 2019)
Obesity hypertension is driven sympathetic neurotransmission to the heart and blood vessels. We tested the hypothesis that high-fat diet (HFD)-induced hypertension is driven by sympathetic neurotransmission to mesenteric arteries (MA) in male but not female Dahl salt-sensitive (Dahl ss) rat. Rats were fed a control diet (CD; 10 kcal% from fat) or HFD (60 kcal% from fat) beginning at 3 weeks (wk) of age; measurements were made at 10-, 17- and 24-wk. Body weight increased with HFD, age and sex. Mean arterial pressure (MAP) was higher in HFD versus CD rats from both sexes at 17- and 24-wk. MA constriction measured using pressure myography, and electrical field stimulation (EFS, 0.2 - 30 Hz) was greater in HFD versus CD in males at 17-wk; this was not due to changes in α2 autoreceptor or norepinephrine transporter (NET) function. Prazosin (α1-AR antagonist) and suramin (P2 receptor antagonist) inhibited neurogenic MA constriction equally in all groups. Arterial reactivity to exogenous norepinephrine (NE; 10(−8) - 10(−5) M) was lower in HFD versus CD at 10-wk in males. Female MA reactivity to exogenous ATP was lower at 24-weeks compared to earlier time points. HFD did not affect tyrosine hydroxylase (TH) or the vesicular nucleotide transporter (VNUT) nerve density in MA from both sexes. NE content was lower in MA but higher in plasma at 24-wk compared to 10- and 17-wk in both sexes. In conclusion, HFD-induced hypertension is not driven by increased sympathetic neurotransmission to MA in male and female Dahl ss rats.